The features’ analysis of modern economic crises - O. I. Esina; R. Zh. Sirazhdinov (Вестник университета)
As evidenced by the historical digression, economic crises are an integral element in the development of the world economy. The overproduction of goods was considered as the main cause of crises, that is, the volume of products produced by aggregate suppliers exceeded aggregate demand. The significant expansion of exports has led to the internationalization of not only world trade, but also the production of goods and the creation of new supply chains, which caused the vulnerability of the entire chain of enterprises connected technologically in many countries. The aim of the work is to study the dynamics of economic crises, to identify their causes and consequences for the world economy. The paper examines the economic crises that have occurred in different countries and the change in their nature. The methods of comparison and statistical analysis were used as research tools in the work. As the analysis carried out in the work has shown, economic crises from partial, covering individual countries, turn into global ones. Moreover, the depth and scale of economic crises are increasing despite the created mathematical tools and a significant increase in computing power. The analysis allows us to draw conclusions about the further regionalization of world trade and production. In addition, these processes are objective and do not depend on the current distribution of economic potential.